2006
DOI: 10.1590/s0100-41582006000100016
|View full text |Cite
|
Sign up to set email alerts
|

Integração de fungicidas à refrigeração no controle de podridão pós-colheita em frutos de meloeiro

Abstract: RESUMOAs podridões pós-colheita constituem fator de risco nas exportações. No entanto, o número de produtos registrados para o tratamento pós-colheita de frutos de melão (Cucumis melo) é reduzido. Objetivou-se neste trabalho avaliar a influência dos fungicidas thiabendazole, azoxystrobin e imazalil a 30, 10 e 400g i.a/100 l, no desenvolvimento de Fusarium pallidoroseum e estudar o efeito deles, combinados à refrigeração, no controle de podridão em melão. Thiabendazole e imazalil inibiram 100% do crescimento mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…For the most aggressive isolate, fruit inoculated with F. falciforme (FSSC) showed reduction of disease severity in the peduncle and epicarp when treated with the active ingredients thiabendazole and azoxystrobin + fludioxonil, respectively. Terao et al (2006), studying the sensitivity of F. pallidoroseum (FIESC) to fungicides, observed that azoxystrobin and thiabendazole efficiently controlled melon lesion severity and size at room temperature. The results of these studies are helpful for improving the management strategies for melon diseases caused by Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the most aggressive isolate, fruit inoculated with F. falciforme (FSSC) showed reduction of disease severity in the peduncle and epicarp when treated with the active ingredients thiabendazole and azoxystrobin + fludioxonil, respectively. Terao et al (2006), studying the sensitivity of F. pallidoroseum (FIESC) to fungicides, observed that azoxystrobin and thiabendazole efficiently controlled melon lesion severity and size at room temperature. The results of these studies are helpful for improving the management strategies for melon diseases caused by Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Both products are systemic, with protective and curative actions. A study carried out by Terao et al (2006) demonstrated efficiency in reducing Fusarium rot in melon caused by F . pallidoroseum when treated with imazalil and thiabendazole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…et Trichothecium roseum sont les maladies les plus importantes du Hami Melons au cours de l'entreposage. La lutte chimique a été largement utilisée contre les maladies de post récolte du melon par trempage dans différentes solutions telles que celles de diméthyl dithio-Carbamate de sodium (Carter 1981 a et b), Imizalil (Carter 1981b), Guazatine (Morris et Wade 1983 ;Huang et al, 2000), Thiabendazole, Azoxystrobin et Imazalil (Terao et al, 2006) ou pulvérisation foliaire avant la récolte par l'Acibenzolar-S-methyl (Huang et al, 2000) et le Benzothiadiazole (Bokshi et al, 2007). Malheureusement, l'usage fréquent des fongicides a été responsable de l'apparition de la résistance des champignons pathogènes et la prise de conscience du consommateur vis-à-vis de la contamination des denrées alimentaires par les résidus de fongicides a orienter la recherche vers la recherche d'autre moyens de lutte.…”
Section: Introductionunclassified
“…O amadurecimento do mamão pode ser retardado pelo uso de inibidores da produção e ação do etileno (ABDI et al, 1998), como o gás 1-metilciclopropeno (1-MCP), e/ou pela aplicação de métodos físicos. Os métodos físicos, a exemplo do tratamento hidrotérmico e da refrigeração, podem ser usados no controle de doenças em póscolheita, atuando diretamente sobre os patógenos, e indiretamente sobre a fisiologia do fruto, retardando os processos bioquímicos de amadurecimento e senescência, reduzindo a taxa respiratória e a transpiração, mantendo a resistência do fruto ao ataque de microrganismos (TERAO et al, 2003).…”
Section: Introductionunclassified